China y América Latina - Wilhelmy von Wolff, Manfred (Estudios Internacionales, 2001)
Relations with China assumed increasing importance within the framework of Latin American international relations in the last decades of the 20th century. In this paper, starting from the current international system, the changes that have taken place domestically at the Chinese economic level are considered, to then analyze the matter from the Latin American perspective, considering the role of the various actors in the region in its relations with China, to finally make a general assessment of the mutual relationship. These are characterized as normal, friendly and of growing political and economic content, although important gaps still exist in the social and cultural dimensions. We argue that from the Latin American perspective, the current Chinese situation favors closer relations, but highly favorable conditions are nevertheless affected by the limitations that still persist.